Effect of Multijunction Approach on Electrical Measurements of Silicon and Germanium Alloy Based Thin-Film Solar Cell Using AMPS-1D - Somenath Chatterjee; Sumeet Singh; Himangshu Pal (International Journal of Photoenergy)
Multijunction solar cells designed from silicon (Si)-germanium (Ge) alloy based semiconductor materials exhibit high theoretical efficiencies (19.6%) compared to the single junction one. The modeling calculations for all solar cells are done by AMPS 1D simulator. The structure of multi-junction i-layer is designed using heterolayers, starting from pure crystalline Si and increase of Ge mole fraction by 25% until pure Ge layer is reached. The top layer has the largest band gap, while the bottom layer has the smallest bandgap. This design allows less energetic photons to pass through the upper layer(s) and be absorbed by the layer below, which increases the overall efficiency of the solar cell. Material parameters required to model the absorber layers are calculated and incorporated in the AMPS 1D simulator for optimizing of solar cell parameter values. Simulation results show that considerable efficiency enhancement can be obtained from the addition of the multi-junction layer.